Knowledge and awareness of nursing students regarding human papillomaviruses infection and vaccination - Mlinar, Suzana (Vojnosanitetski pregled, 2022)
Background/Aim. Human papillomaviruses (HPV) are the most common cause of sexually transmitted infections. Most HPV infections are transient and asymptomatic. Routine vaccination against HPV is the best prophylaxis against HPV infection. The aim of the study was to determine knowledge and risk factors about HPV infection and the attitudes towards vaccination against HPV among nursing students. Methods. This cross-sectional study was conducted on a random sample of 175 nursing students.The students were divided into categories according to their year of studying. Statistical data analysis was done using the t-test and Mann-Whitney U test. Results. Most (93.1%) respondents knew that HPV infection might cause cervical cancer and that it was a sexually transmitted infection (80.0%). Only 31.4% were aware that HPV might cause head and neck cancer, and 22.9% were aware that smoking was a risk factor for HPV infection. Male respondents (p < 0.05) and third-year respondents (p < 0.05) were significantly aware that men could also be infected with HPV. Third-year respondents were significantly aware that early sexual intercourse increased the risk of HPV infection (p < 0.05) and that HPV infection could be asymptomatic (p < 0.05). Respondents under 26 years of age (p < 0.05) and first-year respondents (p < 0.05) were significantly aware that men could as well be vaccinated against HPV. Conclusion. The present study found that the respondents emphasized the importance of health education by nurses and vaccination against HPV. Due to the low vaccination rate of the population, preventive measures are needed to increase public awareness about vaccination against HPV, for which nurses are also responsible.